2012
DOI: 10.1111/j.1469-0691.2011.03709.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of antibiotic administration and outcomes of hospitalized patients with community-acquired and healthcare-associated pneumonia

Abstract: The effects of antibiotic timing on outcomes of patients with community-acquired pneumonia (CAP) are controversial. Moreover, no information is available regarding this issue in healthcare-associated pneumonia (HCAP). We aimed to determine the impact of antibiotic timing on 30-day mortality of patients with CAP and HCAP. Non-immunocompromised adults admitted to hospital through the emergency department (ED) with community-onset pneumonia were prospectively observed from 2001 to 2009. Patients who received prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
2
28
0
2
Order By: Relevance
“…Based on data showing that early appropriate administration of antimicrobials improves outcome in severe sepsis and septic shock, the same premise has been extrapolated to less-severe infections without proof of benefit. In patients with uncomplicated sepsis, the evidence for the timing of antimicrobial administration is contentious [10] and there are no studies substantiating the need for the same approach as is used in severe sepsis or septic shock. In fact, evidence to the contrary has been presented.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data showing that early appropriate administration of antimicrobials improves outcome in severe sepsis and septic shock, the same premise has been extrapolated to less-severe infections without proof of benefit. In patients with uncomplicated sepsis, the evidence for the timing of antimicrobial administration is contentious [10] and there are no studies substantiating the need for the same approach as is used in severe sepsis or septic shock. In fact, evidence to the contrary has been presented.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that CAP carries a mortality rate between 8% and 15% in hospitalized patients [7]. The data concerning the effectiveness of antibiotic timing are controversial in the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…The biological plausibility of these latter associations and their causal relation are Commentary Community-acquired pneumonia: the elusive quest for the best treatment strategy unlikely. The three prospective studies failed to show a significant association between early antibiotic treatment and patient outcomes (5,6,11). These results might stem from a lack of power due to their smaller sample size or from more accurate adjustment for confounding factors.…”
Section: Optimal Time To Antibiotic Initiationmentioning
confidence: 94%